Notonagoro sebagai Homo Significans atas Ideologi Pancasila - Mustansyir, Rizal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
Pancasila—as a representament, interpretant and object—facing a dillematic problem in connection to ideal and a utopiavalues that desired by the founding fathers and undesired activitiesin the real life. Pancasila—as an icon, index and symbol that oughtto give oportunity for other interpretation, so we do not fall into amonolitic interpretation that makes Pancasila become a trivialthing, as in New Era. The power of Pancasila does not lay at themeaning that gave by political elite all, but it depends on allcommunity involvement to belong to Pancasila as a glorioustreasure of Indonesian nation that open to spirit and developmentof the age. Notonagoro is a Pancasila homo significandum for hisattempt to reinterprate national ideology philosophically. He hasused substanstialistical analyzis with refer to the principle words ofeach principles (God, man, one, people, and justice) was anintelligent attempt to placed Pancasila in the abstract, general anduniversal meaning. His concept of Pancasila—abstract, general anduniversal—described the triadic of representament, object andinterpretant.